Intrinsic Linear Dichroism of Organic Single Crystals toward High-Performance Polarization-Sensitive Photodetectors - Wang, Tianyu (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2021 Wiley-VCH GmbH.